Reflections on trust and COVID-19: do politics, medicine and the environment need each other? (UCL Open Environment, 2020)
This short article is centred on how trust can be a valuable resource for developing cognate responses to the COVID-19 pandemic in the medical and social sciences. Politics and medicine can learn from each other. Governments need to persuade individuals to adapt their behaviours, and such persuasion will be all the more convincing in that it is nested in social networks. Trust in government requires consistent (benevolent, performative and joined-up) explanations. The distinction between hard medical and soft social science blurs when patients/citizens are required to be active participants in combatting a pandemic virus.